Hubungan Antara Lingkungan Kerja Dengan Stres Kerja Pada Karyawan Elektronik PT X Di Bekasi - Hilmy Adya Laksana; Netty Merdiaty (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2026)
The research team at PT X in Bekasi set out to determine whether there was a correlation between the stress levels of production division workers and their immediate surroundings. One hundred manufacturing division employees from PT X are the subjects of this quantitative study. Statistical analysis with SPSS software was used to examine the study data. According to the study's findings, there is a negative relationship between the work environment variable and work stress (r=-0.205). As a result, we accept Ha as the alternative hypothesis and reject H0. If researchers want their findings to be more broadly applicable, they should use samples that are more evenly distributed across gender, age, and occupational status in future studies